Characterization of Spacelike Biharmonic Curves with Timelike Binormal According to Flat Metric in Lorentzian Heisenberg Group Heis3 - Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2012)
In this paper, we study spacelike biharmonic curves with timelike binormal according to flat metric in the Lorentzian Heisenberg group Heis(3). We characterize spacelike biharmonic curves with timelike binormal in terms of their curvature and torsion. Additionally, we determine the parametric representation of the spacelike biharmonic curves with timelike binormal according to flat metric from this characterization.
Keywords: Biharmonic curve; Heisenberg group; Flat metric